How Big The Role of Credit Risk, Liquidity Risk and Capital Have an Effect On The Profitability of The 10 Largestt Bank in Indonesia - -, Irawati Junaeni (International Journal of Science, Technology & Management, 2021)
The purpose of this research is to analyze how the effect of credit risk, liquidity risk, bank capital, on profitability. The ratio used to measure credit risk using the Non Performing Loan (NPL), liquidity risk using the Loan to Funding Ratio ( LFR) and bank capital using the Capital Adequacy Ratio (CAR). The sample in this study were the 10 largest banks in Indonesia based on total assets. The analysis technique used in this research is panel data regression with fixed effects. The data processing tool used in this study is the Eviews 10 program. The partial test results show that the variables of credit risk and bank capital have an effect on profitabilityas measured by Return on Assets (ROA). Credit risk shows a negative and significant effect on profitability. And bank capital has a positive and significant effect on profitability. Meanwhile, liquidity risk has no significant effect on profitability. Simultaneously, the variables of credit risk, liquidity risk and capital have an effect of 90.17% on profitability. The remaining 9.83% was influenced by other factors not examined in this study